Saudi Women and Islamic Discourse, Selected Examples of Saudi Feminisms - Al Fassi, Hatoon Ajwad (Hawwa, 2016)
Saudi women entered the realm of writing and language only half a century ago through the genres of both creative and journalistic prose. In this paper, I shall take the example of four Saudi female writers who represent a wide range of intellectual pluralism that runs from conservative to liberal to radical conceptions of state and society, represented in this order by, Nura al-Saad, Suhaila Zain al-Abedin Hammad, Fowziyah Abu Khalid and Wajeha al-Huwaider. This paper will try to answer how and why do gender identities change and in response to what, taking into account that the lives of these women and their literary work represent the continuous search and discovery for, and the reinventing of, themselves. It is important to mark these experiences as part of the complexity of Saudi Arabian intellectual discourse, similar to any society in this respect.